Effect of Seaweed (Sargassum polycystum) Extract on the Levels of Phenolic Compounds in Rubber Tree and Its Application to Induce Resistance Against Phytophthora - โขมพัตร เขมมิการ์; ดีนามอ นุรอามาลี; เชิงเชาว์ นันทา (Princess of Naradhiwas University Journal, 2018)
After foliar spray of rubber tree young seedlings with 0.25 mg/ml of seaweed extract from Sargassum polycystum for 1, 3 and 5 days, the scopoletin was significantly increased for every time point comparing to the control which was sprayed with distilled water. For salicylic acid (SA), it was raised at 1 and 5 days after treatment. The p-coumaric acid was increased only at the 1 day after spraying while the vanillic acid and catechin were not induced by the seaweed extract. After application of seaweed extract to induce resistance in rubber tree seedlings before inoculating with 2x105 zoospores/ml of P. palmivora, it was found that the seedlings with symptom were less than 50% comparing to the positive control. Furthermore, 5 days after Phytophthora infection, levels of the five phenolic compounds and lignin were enhanced including a new isozyme of peroxidase. Differently, the seaweed extract caused the increases of only scopoletin and SA did not induce the accumulation of lignin including the new peroxidase isozyme. The results suggested that the seaweed extract could induce the resistance in rubber tree seedling through the scopoletin, a phytoalexin and the SA signaling of systemic acquired resistance (SAR), but not through the lignin formation.